Enhancing Executive Functioning: The Impact of Cognitive Rehabilitation on Cochlear-Implanted Children - Karim Gharashi; Reza Abdi (Auditory and Vestibular Research)
Background and Aim: Executive Functions (EFs) are essential for learning and self-regulation in children. This study explored the transformative potential of Cognitive Rehabilitation (CR) in enhancing EFs among children with Cochlear Implants (CI). The focus was on assessing key areas of cognitive flexibility, rule acquisition, attention, spatial planning, working memory, and strategy use. Methods: Utilizing a semi-experimental design with pre-test and post-test evaluations, our study focused on children aged 8 to 11 years. A total of 24 children (13 girls and 11 boys) were randomly assigned to either an experimental or a control group. The experimental group underwent 12 sessions of targeted computerized CR, while the control group received no intervention. Post-intervention, we compared the outcomes of both groups. Results: The results revealed a significant improvement in the EFs of the experimental group compared to the control group (p=0.01). These findings underscore the effectiveness of CR in enhancing executive functioning in children with CI. Conclusion: The results of this study showed that cognitive rehabilitation could improve and enhance cognitive flexibility, rule acquisition, attentional set shifting, spatial planning, motor control, working memory capacity, and strategy use.